2005
DOI: 10.3168/jds.s0022-0302(05)73020-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Level Pre- and Post-Puberty and Body Weight at First Calving on Growth, Milk Production, and Fertility in Grazing Dairy Cows

Abstract: The effect of feeding to achieve differential growth rates in Holstein-Friesian (HF; n = 259) and Jersey (n = 430) heifers on time to puberty and first lactation milk production was investigated in a 3 x 2 factorial design. Holstein-Friesian and Jersey calves were reared to achieve a BW of 100 and 80 kg, respectively, at 100 d. At target weight, all calves were randomly allocated to one of 3 feeding treatments to achieve different growth rates. Holstein-Friesian and Jersey calves were fed fresh pasture to achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
76
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 39 publications
11
76
3
4
Order By: Relevance
“…These findings are in line with the studies of Gardner et al (1988), Abeni et al (2000) and Dobos et al (2001), who all showed a positive relationship between BW at first calving and subsequent milk production performance. In contrast, Macdonald et al (2005) found that BW at first calving is important for first lactation milk production, but its effect diminished in subsequent lactations. As reported by Carson et al (2002), heifers reared to calve at 620 kg lost more weight in early lactation and had a longer interval up to the first recorded oestrus than those reared to calve at 540 kg.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…These findings are in line with the studies of Gardner et al (1988), Abeni et al (2000) and Dobos et al (2001), who all showed a positive relationship between BW at first calving and subsequent milk production performance. In contrast, Macdonald et al (2005) found that BW at first calving is important for first lactation milk production, but its effect diminished in subsequent lactations. As reported by Carson et al (2002), heifers reared to calve at 620 kg lost more weight in early lactation and had a longer interval up to the first recorded oestrus than those reared to calve at 540 kg.…”
Section: Discussionmentioning
confidence: 85%
“…The importance of BW and BW gain is supported by the findings of many studies. Macdonald et al (2005) reported that attainment of puberty was influenced by BW gain in their study where BW gain was manipulated by varying feed allowances. This is in line with earlier studies by Arjie and Wiltbank (1971), Short and Bellows (1971) and Foldager et al (1988), whereby level of nutrition and average daily gain (ADG) were reported to significantly reduce the age at which animals reached puberty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An investigation into the effects of different feeding regimes pre-and post-puberty on dairy heifers in New Zealand found no effects of a higher pre-pubertal feed intake on milk production in the first two lactations but those that survived made less milk in lactation 3. Macdonald et al (2005) suggested that the well-fed animals may have had decreased mammary development but compensated initially by an overall greater body size. Others have found that increasing ADG through increasing the plane of nutrition has a minimal impact on histological mammary development (Daniels et al, 2009).…”
Section: Milk Productionmentioning
confidence: 99%
“…Several groups have reported that a younger AFC in dairy heifers does not reduce, or may even increase, the first lactation yields, providing the animals are sufficiently well grown and the AFC is not less than 23 months (Ettema and Santos, 2004;Macdonald et al, 2005;Sakaguchi et al, 2005;Cooke et al, 2013). An AFC below 23 months is however generally detrimental with a large study by Eastham (2012) of UK dairy cows showing that heifers with an AFC < 23 months underperformed by producing less milk in each of lactations 1 to 4.…”
Section: Milk Productionmentioning
confidence: 99%